Blogs de moda e beleza: espaço mercadológico de interação sentido e axiologias - Rodrigues, Graziela Fernanda (2013)
By using the discursive semiotics theories developed by A.J. Greimas, E. Landowski and A.C. Oliveira, it will be investigated how women s Fashion and Beauty blogs named Elfinha and Vende na Farmácia? (Little Elf and Is it Sold on the Drugstore?) engender themselves in lieu of the consumers speeches (bloggers and readers), considering the way by which such virtual spaces have become value objects - as much as for the addressees (consumers and blog readers) involved in this interaction - as for the market and its corporations, who seek for nearness with their respective targets. The research hypothesis states that the dissemination of internet uses has enabled the amplification and diversification of the addressees voice place in mass communications. Nowadays, social networks, virtual pages, discussion forums and blogs present an advantage in terms of information transmission speed and even an efficacy related to traditional medias, once the interaction is more direct and able to produce nearness effects and, therefore, reduce mediations between interlocutors. Especially on the blogs case, the media s nature allows itself to be converted into a place for content production that is availible for everyone to reach. Hence, bloggers and readers have the opportunity to turn themselves into sanctioners that, in the specific cases linked to Fashion and Beauty, lead to a make-consume carried together. In Elfinha and Vende na Farmácia? the interaction happens among bloggers and readers that, equally, are consumers and network users, what brings them close throughout expression and content plans and favors the development of a mutual identification, encouraging the establishment of a communication contract and the dynamic of interaction regimes described by E. Landowski. In the context of a post-modern society, in which an individual s place is established from and by the act of consuming, the modalities (volitional and cognitives) permeate more and more the interactions also within these blogs. Thus, they become another marketing instrument, once they are capable of modalizing their relations with the readers towards a managed interaction, largely held by the manipulation and reactive adjustment regimes. However, the blogosphere professionalization - through relations increasingly regulated by mercadologic initiatives - jeopardize some of the characteristics that have raised its post to a value object: freedom, democratization and authenticity